Intelectual levels and anxiety in children with chronic lead intoxication. Maria Reiche School. Callao-Peru, 2002 - Vega, Julián (2005)
Objectives: To determine the association between both chronic lead intoxication and intellectual levels and between chronic lead intoxication and anxiety in children from Maria Reiche School - Callao. Materials and Methods: A cross sectional and observational study was done in 39 children who had participated in a blood lead screening done by the General Direction of Environmental Health in 2002. The intellectual coefficient was measured and the intellectual level determined; the anxiety checkup list was applied. Children groups were classified according to their blood lead levels in non-poisoned (levels <10 µg/ dL) and poisoned (levels ≥ 10 µg/dL). Chí square and tStudent tests and odds ratio were applied with p<0,05. Results: Poisoned children average intellectual coefficient was 85,5±12,6, and average blood lead levels in children with low intellectual coefficient (border and inferior) 24,4±10,9. The intellectual levels and the blood lead categories were related with p=0,03. Poisoned children presented high risk of deep anxiety (OR=6,33 [IC 95% 1,001-40,071]). T distribution found differences between blood lead levels in the light and deep anxiety groups (p=0,024). Conclusions: We found association between chronic lead intoxication and anxiety degree, but not between intellectual levels and chronic lead intoxication.